Community Empowerment Strategy of Creative Economy Based on Local Potential Development - Luthfiana, Ainul (Prosiding Seminar; 2021: 2021 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.50, 2022)
Progress of the national development paradigm that is moving toward decentralization raises awareness the important of community role as main actor in stimulating economic growth and increasing regional competitiveness. The creative economy is an alternative solution as a new talent to develop the economy by exploring and optimizing the local potential of the region, both natural and human resources as an effort of accelerating village economic recovery after the COVID-19 pandemic. This study aims to formulate a strategy for community empowerment in order to accelerate the development of a creative economy based on local potential. The method used in this research is Community based Research by data collection through observation, interviews, and documentations. Analysis was carried out with stages data collection, condensation, presentation and drawing conclusion. The results obtained indicated that the idea and management of local potential as capital for creative economic development have been pursued by the community yet the lack of direction and assistance by other stakeholders in the context of human capital capacity and flexibility in developing local potential have not been implemented optimally so that it has an impact on slow growth and development of rural economy.